REVITALIZING RURAL LIFE: ZHAOQING'S PUBLIC SPACES REIMAGINED - Zhang, Jiaxin (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2023)
The rural revitalization strategy, first introduced during the 19th National Congress of the Communist Party of China and reaffirmed during the subsequent two sessions in 2021, has emerged as a pivotal and historic initiative in the comprehensive development of a modern socialist nation. This underscores the government's commitment to the holistic rejuvenation and progress of rural regions. In this context, various policy interventions, including urbanization, the development of characteristic towns, and the rural revitalization program, have instigated profound transformations in the economic landscape, social fabric, and architectural structure of rural areas. Consequently, these changes have led to the abandonment of production-oriented public spaces, dispersion of life-oriented public spaces, ecological degradation, and an impact on traditional rural spatial structures and cultural characteristics, resulting in a gradual decline in rural public spaces. This study employs Jiaoyuan Village in Zhaoqing City as a case study to explore the academic rationale behind rural revitalization and rural public spaces. It delves into the reconstruction of rural public spaces, focusing on aspects such as their value, function, and layout. By examining the transformation of Jiaoyuan Village, this research offers insights into the challenges and opportunities associated with rural revitalization efforts and highlights the significance of revitalizing rural public spaces as a means to promote sustainable development in China's countryside